Metabolite and thymocyte development defects in ADA-SCID mice receiving enzyme replacement therapy - Federico A. Moretti (Nature Portfolio, 2021)
Abstract Deficiency of adenosine deaminase (ADA, EC3.5.4.4), a housekeeping enzyme intrinsic to the purine salvage pathway, leads to severe combined immunodeficiency (SCID) both in humans and mice. Lack of ADA results in the intracellular accumulation of toxic metabolites which have effects on T cell development and function. While untreated ADA-SCID is a fatal disorder, there are different therapeutic options available to restore ADA activity and reconstitute a functioning immune system, including enzyme replacement therapy (ERT). Administration of ERT in the form of pegylated bovine ADA (PEG-ADA) has proved a life-saving though non-curative treatment for ADA-SCID patients. However, in many patients treated with PEG-ADA, there is suboptimal immune recovery with low T and B cell numbers. Here, we show reduced thymus cellularity in ADA-SCID mice despite weekly PEG-ADA treatment. This was associated with lack of effective adenosine (Ado) detoxification in the thymus. We also show that thymocyte development in ADA-deficient thymi is arrested at the DN3-to-DN4 stage transition with thymocytes undergoing dATP-induced apoptosis rather than defective TCRβ rearrangement or β-selection. Our studies demonstrate at a detailed level that exogenous once-a-week enzyme replacement does not fully correct intra-thymic metabolic or immunological abnormalities associated with ADA deficiency.